The Breakdown of Friendship and the Post-Covid Mental Health Crisis - Haines, David (Anglican theological review, 2025)
The global health crisis, known as COVID-19, has revealed the already present absence of deep friendships and strong communities in the Western world—contributing to a mental health crisis. In his Nicomachean Ethics, Aristotle suggests that true friends contribute to each other’s growth in virtue. Among the virtues discussed by Aristotle is courage, which is a cardinal virtue from which other virtues such as perseverance and resilience flow. For Aristotle, when you grow in virtue, you increase your ability to deal with those situations which may contribute to a decline in mental health. In this essay, we explore how virtuous friendships contribute to mental health, preventing its decline and strengthening it. We first define friendship and the different types of friendship. We then suggest that though all forms of friendship contribute to mental health, the most important is the virtuous friendship. We conclude with some reflections about how such friendships may be encouraged.